2012
DOI: 10.1166/jnn.2012.6158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Potential on Growth of ZnO Nanorod Arrays Investigated by Electric Force Microscopy

Abstract: The electric and Kelvin force probe microscopy were used to investigate the surface potentials on the ZnO seed layer, which shows a remarkable dependence on the annealing temperature. The optimum temperature for the growth of nanorod arrays normal to the surface was found to be at 600 degrees C, which is in the range of right surface potentials and energy measured between 500 degrees C and 700 degrees C. We demonstrated from both electric and Kelvin force probe microscopy studies that surface potential control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, at comparatively lower beam energy, the secondary electrons are responsible for the pattern with the irradiation zone with a local positive charge (lower beam energy), which attracts the negatively charged ZnO ions to form nanorod arrays selectively in the pattern region only. We have recently shown that the surface potential on the ZnO seed layer depends on the annealing temperature, which modified the growth of ZnO NRs on the seed layer 19 . Therefore, we argue that the electron beam energy modifies the surface potential of the underlying seed layer, which eventually energetically favors the growth of NRs only at lower energy.…”
Section: Resultsmentioning
confidence: 99%
“…However, at comparatively lower beam energy, the secondary electrons are responsible for the pattern with the irradiation zone with a local positive charge (lower beam energy), which attracts the negatively charged ZnO ions to form nanorod arrays selectively in the pattern region only. We have recently shown that the surface potential on the ZnO seed layer depends on the annealing temperature, which modified the growth of ZnO NRs on the seed layer 19 . Therefore, we argue that the electron beam energy modifies the surface potential of the underlying seed layer, which eventually energetically favors the growth of NRs only at lower energy.…”
Section: Resultsmentioning
confidence: 99%